2020
DOI: 10.1186/s41016-020-00202-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the incidence of apoplexy in pituitary adenoma: a single-center study from southwestern China

Abstract: Background: Although the incidence and clinical manifestations of pituitary apoplexy were reported by a few researches, the results are not consistent. This study aimed to explore the risk factors associated with an incidence of apoplexy in pituitary adenomas. Methods: The clinical information of 843 patients with pituitary adenoma from the Department of Neurological Surgery, 1st Affiliated Hospital of Kunming Medical University, was reviewed. The incidence, clinical manifestation, and potential risk factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…[ 7 ] The incidence of PA varies from 0.6% to 22% with different diagnostic criteria. [ 13 ] Li et al . analyzed 2021 cases of PA and recognized male sex, nonfunctioning adenomas, and the presence of macroadenoma as risk factors for its development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 7 ] The incidence of PA varies from 0.6% to 22% with different diagnostic criteria. [ 13 ] Li et al . analyzed 2021 cases of PA and recognized male sex, nonfunctioning adenomas, and the presence of macroadenoma as risk factors for its development.…”
Section: Introductionmentioning
confidence: 99%
“…analyzed 2021 cases of PA and recognized male sex, nonfunctioning adenomas, and the presence of macroadenoma as risk factors for its development. [ 13 ] PA has also been reported with pregnancy[ 18 ] and with various other conditions including hypertension, diabetes mellitus, and increased intracranial pressure. [ 6 ] On the other hand, during the period of coronavirus disease 2019 (COVID-19) pandemic, case reports of PA associated with COVID-19 infection have been sequentially published.…”
Section: Introductionmentioning
confidence: 99%
“…Headache was the most frequent and the earliest of symptoms, which occurred in all of the patients described. This symptom could be explained by the stretching and stimulation of the hypophyseal capsule, with increased intracranial pressure and/or hemorrhage into the subarachnoid space (Li et al 2020). Cranial nerve palsies and systemic symptoms such as nausea and vomiting were also common.…”
Section: Discussionmentioning
confidence: 99%
“…The unique rich vasculature of the pituitary gland, combined with the fragility of the tumor blood vessels can further exacerbate the hemorrhagic tendency. The expanding pituitary tumor, which results from the hemorrhage in the adenoma leads to the compression of the infundibular and hypophyseal vessels, which can ultimately results in pituitary infarction (Blaut et al 2006;Li et al 2020;Abbott and Kirkby 2004;Briet et al 2015;Powell et al 1974). Another study suggested that pharmacological agents may stimulate the growth of the pituitary adenoma and also can have a direct impact on a tumor's microvasculature leading to vasoconstriction with subsequent impairment of oxygen and nutritional supply of pituitary adenomas (Okuda et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, surgery entails great psychological pressure as well as physical discomfort, which can deteriorate patients' social psychological state. Therefore, comprehensive surgery-based treatment strategies that include medical therapies, nursing participation, and psychological intervention play an important role in the postoperative treatment of patients with pituitary adenoma (6,7).…”
Section: Introductionmentioning
confidence: 99%